Reading from the South : African print cultures and oceanic turns in Isabel Hofmeyr's work - Lavery, Charne, 1984-; Nuttall, Sarah (Wits University Press, 2023)
This set of essays analyses the work of Isabel Hofmeyr, globally recognised as one of South Africa's foremost literary and Indian Ocean scholars. The essays elucidate Hofmeyr's path-breaking studies of transnational histories of the book, African print cultures, and cultural circulations in the Indian Ocean world.